2014
DOI: 10.1186/1478-811x-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Hedgehog signaling contributes to the regulation of IGF1 and IGFBP1 serum levels

Abstract: BackgroundHedgehog signaling plays an important role in embryonic development, organogenesis and cancer. In the adult liver, Hedgehog signaling in non-parenchymal cells has been found to play a role in certain disease states such as fibrosis and cirrhosis. However, whether the Hedgehog pathway is active in mature healthy hepatocytes and is of significance to liver function are controversial.FindingsTwo types of mice with distinct conditional hepatic deletion of the Smoothened gene, an essential co-receptor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 54 publications
1
76
0
Order By: Relevance
“…Interestingly, the HCV replication-secretion cycle involves the intracellular pool of PI4P and takes advantage of the VLDL secretory machinery [164166]. Besides damage-induced response, Hedgehog signalling is also active in healthy hepatocytes and contributes to Igf-1 homeostasis [167]. …”
Section: Hedgehog Signalling and Metabolismmentioning
confidence: 99%
“…Interestingly, the HCV replication-secretion cycle involves the intracellular pool of PI4P and takes advantage of the VLDL secretory machinery [164166]. Besides damage-induced response, Hedgehog signalling is also active in healthy hepatocytes and contributes to Igf-1 homeostasis [167]. …”
Section: Hedgehog Signalling and Metabolismmentioning
confidence: 99%
“…Besides JAK2, other upstream regulators of hepatic IGF-1 may mediate its effects, such as FGF21, PPARγ, and components of the hedgehog signaling pathway including Smoothened (66)(67)(68). Furthermore, recent clinical studies have shown ω-3 supplementation and baclofen, a β-p-chlorophenyl derivative of γ-aminobutyric acid (GABA), in increasing plasma IGF-1 concentrations to varying extent (69)(70)(71).…”
Section: Ldlrmentioning
confidence: 99%
“…The latter cells, at least their majority, do not express cilia [1], in contrast to activated HSC. The existence of this unusual type of Hh signalling (cyclopamine responsive) is most evident for healthy hepatocytes [6]. In addition, SMO-independent, truly non-canonical signalling, has been observed at least in part of the cell types (Fig.…”
mentioning
confidence: 98%
“…Although the authors refer to the IHH-positive hepatocytes as ''injured cells'' [1], proof of the actual injury is lacking. Within this context, it should be emphasised that Ihh in normal liver has been recognised as a target gene of Wnt/ß-catenin signalling [10], and, correspondingly, expression could be demonstrated in healthy hepatocytes around the central veins [6,10] where Wnt signalling is highest (cf. [2]).…”
mentioning
confidence: 98%
See 1 more Smart Citation